Management of patients with Arrhythmogenic Right Ventricular Cardiomyopathy in the Nordic countries. (2nd November 2015) - Haugaa, Kristina H.; Bundgaard, Henning; Edvardsen, Thor; Eschen, Ole; Gilljam, Thomas; Hansen, Jim; Jensen, Henrik Kjærulf; Platonov, Pyotr G.; Svensson, Anneli; Svendsen, Jesper H.
Abstract>: Objectives. Diagnostics of patients with arrhythmogenic right ventricular cardiomyopathy (ARVC) are complex, and based on the 2010 Task Force document including different diagnostic modalities. However, recommendations for clinical management and follow-up of patients with ARVC and their relatives are sparse. This paper aims to give a practical overview of management strategies, risk stratification, and selection of appropriate therapies for patients with ARVC and their family members. Design. This paper summarizes follow-up and treatment strategies in ARVC patients in the Nordic countries. The author group represents cardiologists who are actively involved in the Nordic ARVC Registry which was established in 2009, and contains prospectively collected clinical data from more than 590 ARVC patients from Denmark, Norway, Sweden, and Finland. Results. Different approaches of management and follow-up are required in patients with definite ARVC and in genetic-mutation-positive family members. Furthermore, ARVC patients with and without implantable cardioverter defibrillators (ICDs) require different follow-up strategies. Conclusion. Careful follow-up is required in patients with ARVC diagnosis to evaluate the need of anti-arrhythmic therapy and ICD implantation. Mutation-positive family members should be followed regularly for detection of early disease and risk stratification of ventricular arrhythmias.